2010
DOI: 10.1515/cclm.2010.218
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-infection induces major changes in high-density lipoprotein particle size distribution and composition: the effect of antiretroviral treatment and disease severity

Abstract: HIV infection itself may promote major changes in cholesterol distribution among HDL subpopulations that could be partially attenuated by current antiretroviral treatments. Further studies in larger populations are necessary to confirm the impact of HIV on lipoprotein composition and distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…In particular, it has been previously reported that total HDL particle number is reduced during HIV infection (32)(33)(34). However, and in contrast with our present observations, it has been reported that the concentration of cholesterol in large HDL particles was unaltered in HIV-infected patients as compared with uninfected controls ( 32 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been previously reported that total HDL particle number is reduced during HIV infection (32)(33)(34). However, and in contrast with our present observations, it has been reported that the concentration of cholesterol in large HDL particles was unaltered in HIV-infected patients as compared with uninfected controls ( 32 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, it has been previously reported that total HDL particle number is reduced during HIV infection (32)(33)(34). However, and in contrast with our present observations, it has been reported that the concentration of cholesterol in large HDL particles was unaltered in HIV-infected patients as compared with uninfected controls ( 32 ). Interruption of HAART was associated with a reduction in HDL particles of medium and small size ( 35 ), or only in HDL particles of medium size with no change in HDL particles of small size ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“… CD4+ T-lymphocytes (CD4) count in the peripheral blood is an essential tool for the laboratory monitoring of HIV-infected patients, both for the progression of disease and for the assessment of the efficacy of highly active antiretroviral therapy (HAART) [1,2] , but, worldwide, its application was limited due to the expense of equipment and reagents involved. Therefore, it is desirable to find a cheap and effective substitute for CD4 count for the monitoring of immune function of HIV-infected individuals [3] .…”
mentioning
confidence: 99%
“…Consistent with this, the data of Aragones et al showed greater heterogeneity in HIV HDL and increased CE in the larger HDL subfractions. 25 Two observations suggest that increased lipoprotein heterogeneity is due impaired lipoprotein hydrolysis. First, the SEC profiles (Figure 4) showed that all HIV/ART lipoproteins elute earlier than their NL control counterparts; second, these data also show that unlike control TLP, HIV/ART TLP contains a prominent peak for IDL (Figure 4).…”
Section: Discussionmentioning
confidence: 99%